2009
DOI: 10.1002/cphc.200800721
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in the Complex H3N⋅⋅⋅HCl Catalyzed by Encapsulation into a C60 Cage

Abstract: We report proton transfer in the complex H(3)N...HCl to form the ion pair NH(4)(+)Cl(-), which is favored inside the C(60) cage according to quantum chemical calculations. The results show that the NH(4)(+)Cl(-)@C(60) is stable with an interaction energy of -2.78 kcal mol(-1). Compared with the complex H(3)N...HCl without proton transfer, it is found that the C(60) cage plays the role of a catalyst for proton transfer. In NH(4)(+)Cl(-)@C(60) a negative charge area in the C(60) cage is near the cation NH(4)(+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Ma et al . have reported a similar result 31 .
Figure 2MP2/aug-cc-pVTZ level asymmetric single-well potential energy surface (rigid) of H 2 O ··· HCl (left) and H 2 OH + ··· Cl − (right), showing a proton bound to and transferred from the Cl − species, respectively (PBE/6-311 G(d, p) geometry was used for the rigid scan). Bond distances are in Å and the ∠O ··· H–Cl and ∠O – H ··· Cl bond angles in deg.
…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Ma et al . have reported a similar result 31 .
Figure 2MP2/aug-cc-pVTZ level asymmetric single-well potential energy surface (rigid) of H 2 O ··· HCl (left) and H 2 OH + ··· Cl − (right), showing a proton bound to and transferred from the Cl − species, respectively (PBE/6-311 G(d, p) geometry was used for the rigid scan). Bond distances are in Å and the ∠O ··· H–Cl and ∠O – H ··· Cl bond angles in deg.
…”
Section: Resultssupporting
confidence: 64%
“…We estimated the binding energies of the H 2 O···HF dimer in the absence and in the presence of the C 70 cage at various levels of theory, including [CCSD(T)/aug-cc-pVTZ], as was done in previous studies on other systems 13,25,28,31 . From the sign and magnitudes of the uncorrected (Δ E ) and basis set corrected (Δ E (BSSE)) binding energies (Table S1), it is quite apparent that the isolated H 2 O ··· HF dimer is less stable (<1 kcal mol −1 at all levels of theory) than in H 2 O ··· HF@C 70 ; this is accompanied by the O ··· H bond contraction.…”
Section: Resultsmentioning
confidence: 99%
“…35 Quantum chemical calculations show that C 60 catalyzes proton transfer between caged NH 3 and HCl to NH 4 + + Cl À . 36 The greatly improved resolution of the mass spectrometer used in the present study makes it possible to easily separate contributions from protonated, unprotonated and dehydrogenated ions for complexes containing up to three C 60 molecules. Ions are predominantly unprotonated if they contain n o 5 ammonia molecules; the ratio of protonated to unprotonated ions approaches B1 at n = 5 or 6.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known H 3 N−HCl and H 2 O−HCl acid−base pairs provide us with simple and prototypical examples to study proton-transfer reactions. As is known, single H 3 N−HCl and H 2 O−HCl pairs do not react to form ion pairs, H 4 N + Cl − and H 3 O + Cl − , in isolation. However, if there is an external stimulus, such as, polar molecules, ,− excess electrons, , or a nanoconfined environment, , the proton transfer could occur. Li et al and Bowen et al have shown that only a water molecule or an excess electron can trigger the proton transfer of H 3 N−HCl.…”
Section: Introductionmentioning
confidence: 99%